Penerapan Adab Siswa terhadap Sikap Disiplin Siswa di Sekolah Menengah Kejuruan Negeri 3 Ogan Komering Ulu - Aris Eko Cahyono; Rahmat Julius Panjaitan; Dadang Nurdin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aimed to analyze students' moral conduct (adab), students' discipline, and the influence of adab on the discipline of Grade XI DPIB 2 students at SMK Negeri 3 Ogan Komering Ulu. The study employed a quantitative approach with a correlational research design. The sample consisted of 36 students selected using purposive sampling. Data were collected through questionnaires, observations, interviews, and documentation. The research instrument used a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed descriptively to describe each variable, while hypothesis testing was conducted using the Chi-Square test. The findings revealed that students' adab was generally in the moderate category (75.00%), while students' discipline was also classified as moderate (63.88%). The hypothesis testing produced a calculated χ² value of 20.083, which exceeded the critical χ² values at both the 5% significance level (9.488) and the 1% significance level (13.277). Therefore, the alternative hypothesis was accepted, indicating a significant influence of adab on students' discipline. Students with better moral conduct tended to demonstrate higher levels of discipline in complying with school regulations, participating in learning activities, and fulfilling academic responsibilities. These findings emphasize that strengthening adab-based education is an important strategy for developing students' character and improving discipline in the school environment.